2018
DOI: 10.1159/000492716
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cytokines and Verbal Memory in Individuals with Schizophrenia and Their Unaffected Siblings

Abstract: Background: Verbal memory impairment may be considered an endophenotype in schizophrenia (SZ), also affecting the siblings of SZ subjects. Furthermore, the immune-inflammatory system response has an important modulatory effect on brain processes, especially on memory circuits. Objective: Investigating the relationship between TNF-α and IL-6 and memory performance in patients with SZ, their unaffected siblings (SB) and healthy controls (HC). Methods: 35 subjects with SZ, 36 SB, and 47 HC underwent a neurocognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
1
0
0
1
Order By: Relevance
“…The hippocampus, PHC, and amygdala are critical constituents of the cortical and subcortical limbic system and participate in the regulation of emotional reactions, learning, memory, and behavior. In this study, the functional connectivity of the precuneus with the amygdala, hippocampus, and PHC is weakened, which is consistent with the findings of a study by Wen et al (2021), suggesting that the altered connectivity between the precuneus and the limbic system lays the neurobiological foundation for the decline of cognitive function and intensification of negative symptoms in schizophrenia (Berman et al, 2016;Rebouças et al, 2018). Our study also identified decreased FC between the RSC and the PCCR.…”
Section: Within-network Fc Abnormalities In Schsupporting
confidence: 92%
“…The hippocampus, PHC, and amygdala are critical constituents of the cortical and subcortical limbic system and participate in the regulation of emotional reactions, learning, memory, and behavior. In this study, the functional connectivity of the precuneus with the amygdala, hippocampus, and PHC is weakened, which is consistent with the findings of a study by Wen et al (2021), suggesting that the altered connectivity between the precuneus and the limbic system lays the neurobiological foundation for the decline of cognitive function and intensification of negative symptoms in schizophrenia (Berman et al, 2016;Rebouças et al, 2018). Our study also identified decreased FC between the RSC and the PCCR.…”
Section: Within-network Fc Abnormalities In Schsupporting
confidence: 92%
“…Tak więc wynik pracy wydaje się być zgodny z hipotezą, że deficyty w pamięci werbalnej osób ze SZ mogą być wtórne do niewłaściwego funkcjonowania obszarów przetwarzania poznawczego. Nie ma jednak podstaw do przyjęcia, że tło opisanych nieprawidłowości może być innego rodzaju, na przykład proces zapalny [33]. Wykorzystano Skalę Anhedonii Społecznej, Skalę Czasowego Doświadczenia Przyjemności i Kwestionariusz Osobowości Schizotypowej.…”
Section: Inne Problemy Badawczeunclassified